(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
This article aims to understand the relationship between violence and moral values, through the study of three open summaries due to violent crimes. Such documents were produced by the judiciary of the village of Água Branca, in the Sertão of the Province of Alagoas, in the 1880s. For the analysis of this documentation, the legislation of the time, marriage records and microhistory was used as a methodology. In this way, the uses of violence and justice by different social groups are investigated, focusing on a close look at the statements of witnesses, testimonies of the accused, victims and prosecution. Keywords: Violence. Judicial power. hinterland. XIX century.